Sanksi Pidana terhadap Guru yang Melakukan Tindak Penganiayaan kepada Murid saat Proses Pembelajaran - Anak Agung Ngurah Adhi Wibisana; I Made Sepud; I Made Minggu Widyantara (Jurnal Konstruksi Hukum, 2020)
Indonesia has a law on education, namely Law No. 14 of 2005 on Teachers and Lecturers. In its implementation, there is a case that causes pros and cons to the statement of every article of the Teacher and Lecturer Law, especially in relation to the right to defend oneself in criminal acts of persecution. The purpose of this research is to know the arrangement of teaching methods for students during the learning process and to know the criminal sanctions against teachers who abuse students during the learning process. This study uses a normative method with the main data sources namely laws and regulations. The results showed that the element of an act, and / or the result of an act, pain in the body, and injuries to the body contained in Article 351 paragraph (1) of the Criminal Code refers to the Teacher and Lecturer Law, namely in Article 77 paragraph (6). This article defines the basis of persecution, namely actions that cause pain to a person. The criminal act of persecution in the world of education, at least, must be considered with the intention of disciplining and educating the nation's life.